Respostas

2014-07-03T21:44:14-03:00
2x∧2-28x-+48=0
x=[-b+ou-√9b∧2-4ac)]/2a
[28+ou-√(28∧2-4×2×48)]/2×2
[28+ou--√(784-384)]/4
(28+ou-20)/4
x1=(28+20)/4=48/4=12   x1=12
x2=(28-20)/4=8/4=2       x2=2


2014-07-03T23:06:52-03:00
2x² - 28x + 48 = 0
a = 2
b = -28
c = 48
         Δ = b² - 4ac
         Δ = (-28)² - 4 * 2 * 48
         Δ = 784 - 384
         Δ = 400
                    x = - b ± √Δ / 2a
                    x = - (-28) ± √400 / 2 * 2
                    x' = 28 - 20 / 4 = 8 / 4 = 2
                    x'' = 28 + 20 / 4 = 48 / 4 = 12
As raízes da equação são 2 e 12.

Espero ter ajudado. Valeu!